Induction of a Torpor-Like State by 5’-AMP Does Not Depend on H2S Production - Dugbartey, George J.; Bouma, Hjalmar R.; Strijkstra, Arjen M.; Boerema, Ate S.; Henning, Robert H. (PLOS ONE, 2015)
Background Therapeutic hypothermia is used to reduce ischemia/reperfusion injury (IRI) during organ transplantation and major surgery, but does not fully prevent organ injury. Interestingly, hibernating animals undergo repetitive periods of low body temperature called ‘torpor’ without signs of organ injury. Recently, we identified an essential role of hydrogen sulfide (H2S) in entrance into torpor and preservation of kidney integrity during hibernation. A torpor-like state can be induced pharmacologically by injecting 5’-Adenosine monophosphate (5’-AMP). The mechanism by which 5’-AMP leads to the induction of a torpor-like state, and the role of H2S herein, remains to be unraveled. Therefore, we investigated whether induction of a torpor-like state by 5-AMP depends on H2S production. Methods To study the role of H2S on the induction of torpor, amino-oxyacetic acid (AOAA), a non-specific inhibitor of H2S, was administered before injection with 5'-AMP to block endogenous H2S production in Syrian hamster. To assess the role of H2S on maintenance of torpor induced by 5’-AMP, additional animals were injected with AOAA during torpor. Key Results During the torpor-like state induced by 5’-AMP, the expression of H2S- synthesizing enzymes in the kidneys and plasma levels of H2S were increased. Blockade of these enzymes inhibited the rise in the plasma level of H2S, but neither precluded torpor nor induced arousal. Remarkably, blockade of endogenous H2S production was associated with increased renal injury. Conclusions Induction of a torpor-like state by 5’-AMP does not depend on H2S, although production of H2S seems to attenuate renal injury. Unraveling the mechanisms by which 5’-AMP reduces the metabolism without organ injury may allow optimization of current strategies to limit (hypothermic) IRI and improve outcome following organ transplantation, major cardiac and brain surgery.